Extended Study of NUS1 Gene Variants in Parkinson's Disease - Yuan, Lamei; Chen, Xiangyu; Song, Zhi; Le, Weidong; Zheng, Wen; Liu, Xin; Deng, Hao (Frontiers in Neurology, 2020)
Parkinson’s disease (PD), is humanity’s second most common neurodegenerative disorder worldwide. Genetic, environmental factors, and aging are its primary development contributors. Recently the nuclear undecaprenyl pyrophosphate synthase 1 homolog (S. cerevisiae) gene (NUS1) was reported as a candidate gene for PD, which raised our interests in the relationship between NUS1 and PD. This study was aimed to further explore the role of NUS1 variants in PD development. Genetic analysis for 308 Han-Chinese PD patients and 308 ethically matched controls were conducted. Whole-exome or whole-genome sequencing data for 9,762 PD cases reported in 69 articles as well as NUS1 variant data of 494 PD cases in an article were extracted from the PubMed database from July 1, 2011 to July 14, 2020. No potentially pathogenic NUS1 mutation was found in 308 PD cases, and no frequencies bias were observed between 308 PD cases and 308 controls for the only nonsynonymous variant p.Asp179Glu (genotype: χ2 = 0.093, P = 0.761; allele: χ2 = 0.092, P = 0.762). No pathogenic or disease-associated NUS1 variant was reported in the 10,256 PD cases of the 70 articles. In summary, current findings are inadequate to identify NUS1 as a PD candidate gene.